The Effect of Augmented Reality as Learning Media on Table Tennis Learning Interest - Pane, Bessy Sitorus; Mahmuddin; Amansyah; Chairad, Muhammad; Dewi, Rahma (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to see the effect of augmented reality as a learning media on interest in learning table tennis. The research method used is a quasi-experimental method with the research design The Maching Only Pretest-Posttest Control Group Design. The results of this study indicate that the pretest results of students' learning interest show that there is a difference between the average value of learning interest. The average of the experimental class (72.34) is greater than the average value of learning interest in the control class (72.04). To determine whether the difference is significant or not, it is necessary to test the difference. The conclusion in this study based on the results of the t-test shows that the pretest value of learning interest is 0.48 smaller than the t table value at a significant level of 5%. So it can be concluded that there is no difference in the initial ability of experimental and control class students. The prerequisite test results show that the experimental and control class data are normal and homogeneous so that the para-metric statistical test is carried out, namely the t-test. So it can be concluded that there is a significant difference in student learning interest between the experimental class and the control class.